ENGLISH LANGUAGE EDUCATION IN EARLY CHILDHOOD THROUGH THE CHILDREN’S SONGS - Seriadi, Si Luh Nyoman (Yavana Bhasha : Journal of English Language Education, 2018)
The development of the global world has demanded the children of today to grow faster and compete more closely. One ability they should have to be able to compete with the globalization is ability to communicate in English. As we know that the ability of children to absorb a variety of information around it is extraordinary. So, when we want a child can have a good ability in communicating with English, English learning should be done since the early phase. But in practice, there are some obstacles encountered such as the children difficulty in understanding the subjects of this foreign language. This is reasonable because the position of English in Indonesia is as a foreign language. To overcome these obstacles, it requires effective learning techniques, appropriate, and interesting so that learners are motivated to learn this foreign language. To create a fun English classroom atmosphere, one of them is with the use of songs for learning media.Keywords: English Education, Early Childhood, Songs